The Relationship between Gadget Abuse and Student Learning Motivation at SMP Negeri 25 Padang - Ibna, Resti Hidayatul; Ardi, Zadrian (Universitas Negeri Padang, 2022)
The development of an increasingly sophisticated era, especially in the field of technology, one of which is gadgets, so that it can have positive and negative impacts on its users. One of the negative impacts is the excessive use of gadgets on students, in their use students are not able to limit them so that it causes a decrease in student motivation in learning. This study aims: (1) to describe gadget abuse among students, (2) to describe student learning motivation, and (3) to examine the relationship between gadget abuse and junior high school students' learning motivation. This study uses a quantitative approach with a correlational type. The subjects of this study were 263 students using the Simple Random Sampling technique. The instrument used was a questionnaire using a Likert scale. Data were analyzed using descriptive statistical techniques and to examine the relationship between gadget misuse and learning motivation, the Pearson product moment correlation technique was used. The results showed that: (1) gadget abuse is generally in the high category, (2) learning motivation is in the medium category, and (3) there is a negative relationship between gadget abuse and student motivation with a correlation coefficient of -0.346 and a significance level 0.001. Based on the results of the research, it is expected that counseling teachers can provide assistance in the form of information guidance services, group guidance services, so that they are able to increase learning motivation well.